Ensuring a sustainable supply of aquatic products in the future: research on the promotion and application of deep-sea aquaculture - Ma, Ye; Zhang, Ying (Frontiers in Nutrition, 2025)
Fisheries are an important source of protein for humans. Currently, freshwater and coastal aquaculture fisheries, as well as capture fisheries, have reached saturation point in terms of development potential and are severely polluted, making the supply of aquatic products unsustainable. Deep-sea aquaculture utilizes the vast exploitable space of the open sea, breaking through the limitations of coastal waters and land. It directly increases the global supply of high-protein aquatic products through large-scale and green aquaculture, playing an important role in ensuring the sustainable supply of aquatic products in the future and meeting human nutritional needs. Therefore, based on the assumptions of bounded rationality and stakeholder interdependence, this study constructed an evolutionary game model to analyze how to promote the application and implementation of deep-sea aquaculture. The conclusions of the study are as follows. First, this study affirms that the government plays an important role in promoting and applying deep-sea aquaculture, but government intervention cannot be sustained. Second, blind government intervention is not beneficial and may lead to a double failure of government and market. Finally, compared to the expected total profits from deep-sea aquaculture, it is more important to identify risk and cost thresholds and establish a fair mechanism for sharing benefits and risks. This threshold is defined as the total risk and costs should be less than the sum of potential profits and government subsidies. The research conclusions indicate that the government’s role in the promotion and application of deep-sea aquaculture should evolve in tandem with the industry’s maturity, transitioning from a “leading role in the initial phase” to a “guiding role in the mature phase.” Additionally, the fundamental approach to promoting the widespread adoption of deep-sea aquaculture lies in establishing a cooperative mechanism between aquaculture enterprise and service organization under the guidance of market mechanisms. This study aims to explore how to promote deep-sea aquaculture to enhance the sustainable supply of global aquatic products, thereby expanding and securing channels for human food and protein supply.